A Framework Proposal to Follow‐Up on Preclinical Convulsive Signals of a New Molecular Entity in First‐in‐Human Studies Using Electroencephalographic Monitoring. Issue 5 (31st May 2019) - Abt, Markus; Dinklo, Theo; Rothfuss, Andreas; Husar, Elisabeth; Dannecker, Robert; Kallivroussis, Katja; Peck, Richard; Doessegger, Lucette; Wandel, Christoph
Abstract : Traditionally, in dose‐escalating first‐in‐human (FiH) studies, a dose cap with a 10‐fold safety margin to the no observed effect level in animals is implemented if convulsive events are observed in animals. However, the convulsive risk seen in animals does not generally translate to humans. Several lines of evidence are summarized indicating that in a dose‐escalating setting, electroencephalographic epileptiform abnormalities occur at lower doses than clinical convulsive events. Therefore, we propose to consider the occurrence of epileptiform abnormalities in toxicology studies as premonitory signals for convulsions in dose‐escalating FiH studies. Compared with the traditional dose‐cap approach, this may allow the exploration of higher doses in FiH and, subsequently, phase II studies without compromising human safety. Similarly, the presence or absence of electroencephalographic epileptiform abnormalities may also aid the assessment of proconvulsive risk in situations of increased perpetrator burden as potentially present in pharmacokinetic and/or pharmacodynamic drug–drug interactions.